Impact of tissue culture banana technology on farm household income and food security in Kenya - Kabunga, N.S.; Dubois, T.; Qaim, M. (Georg-August-Universität Göttingen, 2011)
While tissue culture (TC) technology for vegetative plant propagation is gradually gaining in importance in Africa, rigorous ex post assessments of welfare effects for smallholder farm households is lacking. Using recent survey data and accounting for self-selection in technology adoption, we analyze the impacts of TC banana technology on household income and food security in Kenya. To assess food security outcomes, we employ the Household Food Insecurity Access Scale (HFIAS) – a tool that has not been used for impact assessment before. Estimates of treatment-effects models show that TC banana adoption increases farm and household income by 153% and 50%, respectively. The technology also reduces relative food insecurity in a significant way. These results indicate that TC technology can be welfare enhancing for adopting farm households; its use should be further promoted through upscaling appropriate technology delivery systems.